Sistem Informasi E-Commerce Berbasis Web pada Usaha Keripik Ms - Yunita Tiva; Ferdinandus Lidang Witi; Benediktus Yoseph Bhae (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2025)
The MS Chips business is a micro-enterprise with a limited market reach, a small workforce, and is independently managed by the owner. The business was founded in 2000 with the aim of improving human resources and empowering families to increase income and help children struggling to find work. Its main products include regular cassava chips, Nuabosi cassava chips, and banana chips. With the advancement of technology, businesses are required to adapt to compete in the digital era. Technology facilitates the rapid, precise, and accurate access to information, helping to simplify daily activities. Through the use of technology and internet access, people can easily obtain information about product availability, flavor variants, and prices through devices such as laptops, tablets, and smartphones. The purpose of this study is to design a web-based e-commerce information system for the MS Chips business, a case study of the MS Chips Factory. Thus, the application of technology is expected to expand marketing reach and increase the competitiveness of the MS Chips business amidst the development of the digital economy.